Accounting And Accountability In Islamic Religious Organizations : A Case Study Of Pesantren In The Province Of Nanggroe Aceh Darussalam - Indonesia - Basri, Hasan (2010)
This study concerns the perceptions of Muslim scholars regarding how the Islamic religious organizations demonstrate their financial accountability and the role of financial reporting in enhancing such accountability, as well as the practice of accounting and accountability in a selected pesantren in the Nanggroe Aceh Darussalam (NAD) province, Indonesia. The study takes a qualitative approach in which the data is mainly derived from semi-structured interviews and relevant documentary materials as well as observation of the pesantren daily life. The findings suggest that the “Muslim scholars” interviewed have concerns regarding accounting and accountability practices in Islamic religious organizations. The majority of Muslim scholars interviewed pointed out that Islamic religious organizations have an obligation to be accountable to society, such as to the donors and their beneficiaries and to God as well. They emphasize that accountability in Islam is understood as being broader than what is generally understood in conventional accountability, which is not deemed to extend beyond human society. It is clearly stated that accounting and accountability activities play a very significant role in Islamic history and that they are part of the sacred activities, as the division between religious and secular is unknown in Islam.